P.S. I still hate it here : (Abrams Image, 2012)
On the heels of the successful P.S. I Hate it Here comes an all-new, even more outrageous and laugh-out-loud funny collection of real letters written by children ages eight to sixteen to their parents about their adventures at summer camp. Written with the same wit and honesty that made the first book a runaway hit, these new letters take the reader on a familiar adventure that conjures up the experience of being away from home, and the hilarious and lasting memories that accompany that special place called sleepaway camp.